Dissipative soliton resonance in a full polarization-maintaining fiber ring laser at different values of dispersion - Armas Rivera, I. (2016)
We investigated the dissipative solitons resonance in an ytterbium-doped fiber ring laser in which all the elements are polarization maintaining (PM). A semiconductor saturable absorber mirror was used as a mode-locker. The cavity included a normal dispersion single-mode fiber (SMF) and an anomalous dispersion photonic crystal fiber. The change of the length of the PM SMF allows the variation of the net-normal dispersion of the cavity in the range from 0.022 ps2 to 0.262 ps2. As the absolute value of the net-normal dispersion increases from 0.022 ps2 to 0.21 ps2, a square-shaped single pulse transformed to a single right-angle trapezoid-shaped pulse, and, at the dispersion of 0.262 ps2, to multiple right-angle trapezoid-shaped pulses, per round-trip.